Authoritarianism as a “Wicked Problem” in Contemporary International Relations - Ficek, Ryszard (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2022)
This study aims to explore the concept of authoritarianism, which – presented in terms of the “wicked problem” of the contemporary world – seems to be a severe challenge to present-day International Relations (IR), both theoretically and practically. The author of the article defines the concept of authoritarianism as a form of the political system in which the power and material resources of the state have been centralised, appropriated, and put at the disposal of either an individual or an elitist group “in power.” In this way, the possibilities of integrating the authoritarian state – both politically and economically – with the global system of international relations are limited, and the vital administrative institutions of the state have been manipulated and appropriated. The applied research method allows for interpreting the discussed issues in a complex – albeit specific – systemic form, characteristic not only for politically fragile or declining countries and regions but also for politically stable and economically developed ones. The author’s analysis allows for the presentation and reinterpretation of the issue of contemporary authoritarian regimes concerning international relations in terms that not only define but often legitimise some of the most despotic, autocratic, and hegemonistic forms of the political systems in modern times.